ANALYSIS OF BLACK SPOTS ON JL. RAYA KAKAP KUBU RAYA DISTRICT WITH Z-SCORE METHOD - Azwansyah, Heri (Jurnal Teknik Sipil, 2024)
Kubu Raya is a district in West Kalimantan Province. It is directly adjacent to Pontianak City, the province's capital. This condition increases mobility and vehicle traffic, resulting in a relatively high accident rate.Traffic accident data came from the Kubu Raya Regency Police Station, and field observations obtained data on road condition and completeness. The analysis methods used are weighting, Z-Score, and CUSUM (Cumulative Summary).The number of accidents in Jalan Raya Kakap during 2020 - 2022 amounted to 26 incidents. The characteristics of traffic accidents on Jalan Raya Kakap for three years (2020 - 2022) are that victims with minor injuries are more than victims of death and serious injuries, namely seven victims in 2020, 8 victims in 2021, and 18 victims in 2022. STA points 0 - 1 have the highest number of accidents during the 3-year period, which is 152 STA points. 2-3 by 129, and point STA. One black spot falls into the high accident vulnerability category: point STA. 0-1. Two black spots fall into the high accident vulnerability category: STA points. 2-3 and STA. 7-8. Four black spots fall into the medium category. Three black spots fall into the low category. Moreover, four points are categorized as not accident-prone.